FRYDERYK CHOPIN, A FORERUNNER OF THE HARMONY OF THE 20ᵗʰ CENTURY - Dedicated to Fryderyk Chopin’s 200ᵗʰ Birth Anniversary - - COCA, Gabriela (Studia Universitatis Babes-Bolyai Musica, 2010)
Fryderyk Chopin, one of the greatest creators of the 19th century is still enigmatic until nowadays regarding to the energetic – spiritual sources of his music, to the micro and macro systems of his musical language, taking into consideration the harmonic innovations that can predict modern sonorous harmonic elements.